Urocortins exhibit differential effects on PGE2 and PGF2α output via CRHR2 in human myometrium. Issue 1 (27th May 2021) - You, Xingji; Chen, Zixi; Sun, Qianqian; Yao, Ruojin; Gu, Hang; Ni, Xin
Abstract : Urocortins (UCNs), belonging to corticotropin-releasing hormone (CRH) family, exert their function via CRH receptor type 1 (CRHR1) and 2 (CRHR2). Our previous studies have demonstrated that CRH acts on CRHR1 to potentiate prostaglandins (PGs) output induced by inflammatory stimuli in myometrial cells. In the present study, we sought to investigate the effects of UCNs on prostaglandin (PG) output via CRHR2 in cultured human uterine smooth muscle cells (HUSMCs) from pregnant women at term. We found that UCN and UCN 3 treatment promoted PGE2 and PGF2α secretion in a dose-dependent manner. In contrast, UCN2 dose-dependently inhibited PGE2 and PGF2α secretion. Their effects were reversed by CRHR2 antagonist and CRHR2 siRNA. Mechanically, we showed that UCN and UCN3 suppressed cAMP production and led to Gi activation while UCN2 stimulated cAMP production and activated Gs signaling. Further, UCN and UCN3 but not UCN2 activated NF-κB and MAPK signaling pathways through Gi signaling. UCN and UCN3 stimulation of PGs secretion were dependent on Gi/adenylyl cyclase (AC)/cAMP, NF-κB and MAPK signaling pathways. UCN2 suppression of PGs output was through Gs/AC/cAMP signaling pathways. Our data suggest that UCN, UCN2 and UCN3 can finely regulate PGs secretion via CRHR2, which facilitates the functional status of the uterus during pregnancy.